BANKING ETHICS AND UNFAIR CONTRACT TERMS: EVIDENCE FROM CONVENTIONAL AND ISLAMIC BANKS IN MALAYSIA - Noor Mahinar Abu Bakar; Norhashimah Mohd Yasin; Ng See Teong (Journal of Islamic Management Studies, 2020)
The ethical peril of unfair contract terms is evident from the abuse of banks’ dominant position relative to bank consumers in dictating contractual terms and conditions, and asymmetrical information that causes significant imbalance of rights and obligations of bank consumers as the weaker contracting parties, placing them at a detriment. This study examines the tenets and underlying concepts of banking ethics in conventional and Islamic banks in protecting bank consumers from unfair terms in consumer contracts. This is a qualitative-based research using content analysis approach in analyzing the basics and differences between conventional and Islamic banking ethics to counter unfair terms. It is found that while Islamic banking ethics are characteristically underpinned in religion and Shariah principles, some other ethical values do bear resemblance to the ethical ideals promoted by the conventional bank. Also, good governance of the banking sector requires incorporation of ethical banking practices to complement the demands of consumer protection law towards effective protection against unfair terms. This study is of important interest to Malaysian financial regulators, bankers and bank consumers alike since the upholding of proper banking ethics would contribute to positive relationship between banks and bank consumers while advancing sustainable development of Malaysian banking industry.